The effectiveness of exercise interventions to prevent shoulder injuries in athletes: a systematic review and meta-analysis - Swart, J. J. W.; Myburg, N.; Benita, O. (British Journal of Sports Medicine, 2021)
Background The literature supports exercise to avert injuries in the lower extremity and injuries in general. Nevertheless, the utilisation of exercise strategies to prevent sports-related shoulder injuries remain unproven. This systematic review`s primary aim is to evaluate the effectiveness of exercise interventions to prevent shoulder injuries in athletes.